Elucidation of the Solid Electrolyte Interphase Formation Mechanism in Micro‐Mesoporous Hard‐Carbon Anodes. Issue 8 (23rd November 2021) - Alptekin, Hande; Au, Heather; Olsson, Emilia; Cottom, Jonathon; Jensen, Anders CS; Headen, Thomas F.; Cai, Qiong; Drew, Alan J.; Crespo Ribadeneyra, Maria; Titirici, Maria‐Magdalena
Abstract: The microstructure of hard carbons can be designed to maximize their performance as anodes for sodium‐ion batteries. However, the nature of the electrolyte is also decisive in the capacity and long‐term stability. Here, hard carbons with a tailored bimodal pore network of internal micropores interconnected through mesopores are studied as sodium‐ion battery anodes. The evolution of their solid electrolyte interphase (SEI) is analyzed in three different electrolytes (NaPF6 in an ether‐based solvent, and NaPF6 or NaClO4 in a carbonate‐based system). Combining experiments with density functional theory calculations, it is proposed that formation of the SEI is mainly controlled by the decomposition of the salt anion. This process occurs through the intermediate functionalization of the carbon surface by the decomposed anion fragments. It is suggested that the innermost SEI sub‐layer governs the performance and long‐term stability of the anode. While the presence of a fluorine‐containing salt appears to have a determining role in the SEI stability, the electrochemical decomposition of carbonate‐based solvents is detrimental for the long‐term stability as the interfacial resistance increases. In contrast, the ether‐based system enables stable long‐term cycling as the interphase remains almost intact once the first fluorine‐rich SEI layer is formed. Abstract : Hard carbons with tailored bimodal porosities are studied as sodium‐ion anodes. Decomposition of the electrolyte salt anion (PF6 − /Cl − ) and the nature of the innermost solid electrolyte interphase (SEI) sub‐layer controls the SEI evolution. The fluorine‐containing salt enables a stable SEI, although electrolyte decomposition is greater in carbonate‐based solvents; in ether‐based systems, the SEI remains mostly unaltered once the first fluorine‐rich layer is formed.